Analisis Strategi Pemasaran Keramik Lantai Menggunakan Metode SWOT pada PT.XYZ - Khusen Rifai, Achmad; Nuriyanto (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to formulate an effective and sustainable marketing strategy for PT. XYZ in response to the declining sales of ceramic floor tiles from 2021 to 2024. The research employs a descriptive quantitative method by utilizing SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis to evaluate internal strengths and weaknesses, as well as external opportunities and threats that influence marketing performance. Data were collected through interviews with marketing decision-makers, documentation of sales reports, and direct observation of the company’s marketing activities. The SWOT analysis revealed several strategic issues, including limited promotional outreach, fluctuating customer demand, pricing pressure from competitors, and untapped market opportunities. Based on the SWOT matrix, strategic alternatives were formulated by combining internal and external factors into four categories: SO (Strength–Opportunity), WO (Weakness–Opportunity), ST (Strength–Threat), and WT (Weakness–Threat). The findings indicate that the most crucial strategy is to enhance digital marketing and promotional activities, particularly through online platforms and social media. Additional strategies include the development of environmentally friendly products and the formation of strategic distribution partnerships to expand market reach. These strategies are expected to strengthen PT. XYZ’s competitive position, align with evolving consumer trends, and increase overall market share. The study concludes that the application of SWOT analysis offers a structured and practical framework for identifying marketing priorities. Consequently, the SWOT-based strategic analysis places PT. XYZ in Quadrant I, supporting an aggressive strategy. This approach is beneficial as it leverages the company's strengths to seize external opportunities such as market penetration, product development, vertical integration, and diversification. Keywords: marketing strategy; SWOT analysis; ceramic industry; strategic planning;IFAS and EFAS Matrix